Health-Related Quality of Life in Patients with Chronic Obstructive Pulmonary Disease - Masroor DD; F Rafii; Fadaeeaghdam N; Hoseini AF (Iran University of Medical Sciences, 2012)
Background & Aim : complications of chronic obstructive pulmonary disease (COPD) frequently lead to impaired social life , physical Function and daily activities in these patients and finaly the health-related quality of life (HRQL) of these patients will decrease . The aim of this study was to determine HRQL and its relationship with some demographic variables.   Material & Methods: using a cross-sectional descriptive design, 331 COPD patients admitted to hospitals affiliated with Tehran University of Medical Sciences were recruited by constant sampling. Data collection tools included demographic information form and HRQL questionnaire (SF-36). Data was analyzed using SPSS ) v . 16 ( , descriptive statistics and Pearson correlation coefficient, ANOVA and Independent t- test.   Results: the findings showed a reduction in HRQL especially in physical health dimension. Significant relationships were found between HRQL and some demographic characteristics such as gender, education level, duration of disease, type of medication and hospitalizations frequency during the past year (P <0.05). Conclusions: Regarding the relationship between HRQL and some demographic variables, using appropriate caring approaches such as executing educational programs about adequate activity, breathing exercices, techniques promoting breathing pattern and right ways of using medications in COPD patients is recommended